Comparative Performance of Large-Cap and Mid-Cap Mutual Funds Across Market Cycles in India - B.S. Deepa; Mohd Jameel; Mohammed Furquan; Tousheeba Toufeeq (Involvement International Journal of Business, 2025)
Mutual funds play a vital role in balancing returns and risks for investors, particularly across different market phases. This study investigates the comparative performance of the Motilal Oswal Mid Cap Fund and the HDFC Large Cap Fund during bull, bear, and recovery markets from 2014 to 2024. A quantitative approach was employed using performance metrics such as returns, volatility, Sharpe ratio, Sortino ratio, alpha, and compound annual growth rate (CAGR). Benchmark indices (Nifty Midcap 150 and Nifty 100) were used for comparison. Findings revealed that during the bull phase (2014–2017), the mid-cap fund achieved returns of 0.570, though below its benchmark of 0.682, while the large-cap fund outperformed its benchmark (0.367 vs. 0.322). In the bear phase (2018–2020), both funds showed negative Sharpe ratios and alphas, with the large-cap fund exhibiting greater downside protection. In the recovery phase (2021–2024), the mid-cap fund delivered a CAGR of 36.59%, surpassing its benchmark (22.35%), while the large-cap fund maintained steady growth (17.79% vs. 11.61%). The results confirmed the trade-off between returns and volatility, consistent with modern portfolio theory. Mid-cap funds demonstrated higher growth potential during recoveries but carried higher risks, while large-cap funds offered stability and better risk-adjusted returns across cycles. These insights are consistent with previous research on investor risk preferences and market resilience. While the study provides valuable insights into fund performance across market phases, its scope is limited to two funds and a single domestic market. Future studies should include broader samples, cross-market analyses, and qualitative dimensions of fund management to strengthen understanding of fund resilience and growth dynamics.